PEMANFAATAN MEDIA WORDWALL DALAM PEMBELAJARAN LINTAS BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Faizatul Mariska; Bagus Aji Danan Jaya Ilmi; Anindya Dwi Setya Rahayu; Ika Dian Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of Wordwall media in cross-cultural learning to improve students' learning outcomes. The study employed a quantitative approach using a One Group Pretest-Posttest Design. The subjects consisted of 17 fourth-grade students at SDN Buluh 1. Data were collected through pretest and posttest instruments containing 10 multiple-choice questions. The data were analyzed using descriptive statistics and N-Gain analysis. The results showed that the average pretest score was 61.76 and increased to 84.12 in the posttest. The N-Gain value was 0.58, categorized as moderate improvement. The classical learning mastery reached 88.24%. These findings indicate that Wordwall media can improve students’ learning outcomes in cross-cultural learning by creating an interactive and enjoyable learning environment.